Hand-to-mouth work culture and the COVID-19 lockdown restrictions: experiences of selected informal sector workers in Kumasi, Ghana - Adom, Dickson; Adu-Mensah, Jephthar; Sekyere, Paul Appiah (Research Journal in Advanced Humanities, 2020)
This study investigated the economic impacts of the COVID-19 restrictions on businesses and livelihoods. Study participants included 25 informal sector workers who were sampled purposively and conveniently. Qualitative thematic analysis was used for interpreting the data generated from the study. The findings revealed that these workers were adversely affected economically by the COVID-19 lockdown and other restrictions, disrupting their business operations, and plunging their livelihoods into extreme poverty. It was also revealed that the high number of informal sector workers in the 'hand-to-mouth' work culture category in Kumasi cited to have flouted the COVID-19 lockdown regulation due to the unbearable economic surge it had inflicted on their livelihood support systems. The study suggests that immediate economic mitigation strategies set out by the Coronavirus Alleviation Programme (CAP) as well as financial agencies must factor the economic needs of the informal sector workers in the hand-to-mouth work culture category and offer them robust financial relief to assist them recover from economic impacts due to the COVID-19.